An automatic skill evaluation framework for robotic surgery training. Issue 1 (17th October 2018) - Peng, Wenjia; Xing, Yuan; Liu, Ruida; Li, Jinhua; Zhang, Zemin
Abstract: Background: To provide feedback to surgeons in robotic surgery training, many surgical skill evaluation methods have been developed. However, they hardly focus on the performance of the surgical motion segments. This paper proposes a method of specifying a trainee's skill weakness in the surgical training. Methods: This paper proposed an automatic skill evaluation framework by comparing the trainees' operations with the template operation in each surgical motion segment, which is mainly based on dynamic time warping (DTW) and continuous hidden Markov model (CHMM). Results: The feasibility of this proposed framework has been preliminarily verified. For specifying the skill weakness in instrument handling and efficiency, the result of this proposed framework was significantly correlated with that of manual scoring. Conclusion: The automatic skill evaluation framework has shown its superiority in efficiency, objectivity, and being targeted, which can be used in robotic surgery training.